Fostering self-efficacy in Chinese university athletes: the mediating roles of psychological resilience and emotional regulation and the moderating role of autonomy-supportive coaching - Zhang, Xiao; Khan, Safeer Ullah (Frontiers in Psychology, 2025)
This study explores how mental toughness contributes to the psychological sustainability of athletes by enhancing emotional regulation and psychological resilience, ultimately fostering self-efficacy, particularly in environments supported by autonomy-supportive coaching. The study examines mental toughness (MT), a dispositional resource for goal-focused persistence under pressure, and its effects on performance self-efficacy (PSE) through the mediating roles of emotional regulation (ER) and psychological resilience (PR), with autonomy-supportive coaching (ASC) as a contextual moderator. University athletes in China face intense dual academic-athletic demands within a collectivist culture that may suppress autonomy and undermine self-efficacy, yet little research addresses how psychological and coaching factors jointly shape their confidence. Using purposive sampling, we recruited 581 active university athletes across China who met the eligibility criteria: (1) currently enrolled as a university student, and (2) actively participating in organized sports for at least one year. Participants completed validated scales measuring the target constructs. We analyzed the data through structural equation modeling (SEM) in Smart PLS. Results reveal that MT positively affects ER and PR, which in turn significantly enhance PSE. Both ER and PR mediate the relationship between MT and PSE, while ASC strengthens the positive effects of MT on ER and PR. Theoretically, the study highlights the role of internal psychological resources and supportive environments in sustaining athlete development over time, offering a framework that bridges sport psychology with broader concepts of personal and developmental sustainability. The study provides practical guidance for coaches aiming to foster mental toughness and psychological skills to improve athletes' confidence and psychological resilience.